KUALITAS SDM, MOTIVASI, DISIPLIN, KOMPENSASI, DAN KINERJA PERANGKAT DESA DI KECAMATAN SAMBELIA - Mustiadi, Mustiadi; Muawanah, Umi; Farhan, Djuni (Universitas Hamzanwadi, 2023)
The aim of this research is to find out and explore the influence of the quality of human resources, motivation, discipline and compensation on the performance of village officials in the Sambelia sub-district, East Lombok district. The population in this study was all Village Officials in the Sambelia sub-district, East Lombok Regency, totaling 187 people, and based on the full sample technique, namely the entire population. Thus, the samples in this study were a number of collected questionnaires which had been distributed by the researcher to all Village Apparatus in the Sambelia Sub-district. East Lombok Regency. The number of samples in this research was 155 respondents. This research includes quantitative descriptive research (descriptive quantitative research), namely research that aims to describe or describe the properties (characteristics) of a situation or research object carried out through collecting quantitative data analysis and statistical testing. The research results explain that 1). The quality of Human Resources partially influences the performance of Village Officials in the Sambelia District, East Lombok Regency. 2). Motivation partially influences the performance of Village Officials in Sambelia District, East Lombok Regency, 3). Discipline has a partial effect on the performance of Village Officials in Sambelia District, East Lombok Regency, 4). Compensation has a partial effect on the performance of Village Officials in the Sambelia District, East Lombok Regency, 5). The quality of human resources, motivation, discipline and compensation simultaneously influence the performance of Village Officials in the Sambelia District, East Lombok Regency.